The New Future of Work: Research from Microsoft into the Pandemic’s Impact on Work Practices - Teevan, Jaime; Hecht, Brent; Jaffe, Sonia; Baym, Nancy; Bergmann, Rachel; Brodsky, Matt; Buxton, Bill; Butler, Jenna; Coleman, Adam; Czerwinski, Mary; Houck, Brian; Hudson, Ginger; et al. (Microsoft, 2021)
The coronavirus pandemic not only caused a public health crisis, it also caused technological, social, and cultural disruption. This past year, people across the globe experienced a rapid shift to remote work that upended their existing practices and will have long-term implications for how work gets done in the future. Looking forward, we expect that some of those who used to work from offices will continue to work remotely, while others will adopt hybrid models that will involve a combination of working from the office and working remotely. The current moment presents a unique opportunity to understand the nature of work itself, to improve remote support for a range of work practices, and to use what we have learned through remote work to improve in-office and hybrid practices. As a company whose mission is to empower every person and every organization on the planet to achieve more, it is vital that Microsoft understands the massive transition currently underway so that we can help our customers come through this challenging time stronger and more resilient. We are all right now participants in a giant, natural, uncontrolled remote work experiment from which Microsoft must learn. Just as research has been fundamental in developing ways to prevent and treat COVID-19, it is also fundamental to understanding and supporting evolving the sociotechnical work practices. At the start of the pandemic, researchers from across Microsoft formed an ongoing cross-company initiative to coordinate efforts with the goal of understanding the impact of remote work and identifying opportunities to support new working practices. The initiative consists of over 50 research projects conducted by teams that span a range of disciplines (including engineering, research, marketing, human resources, and facilities) and divisions (including Microsoft Research, Office, Windows, Azure, Xbox, GitHub, and LinkedIn). The projects employ many different methodologies, ranging from small-scale, formative interviews with customers to large-scale modeling exercises and even EEG measurements of electrical impulses in the brain. This report provides a synthesis of the findings from these many research projects. We believe it represents the largest compilation of research related to the pandemic’s impact on work practices available to date. The findings highlight a number of acute challenges and suggest opportunities to develop new work practices that are more efficient, equitable, and energizing. Work will never again be the same. With care and effort, however, we hope to make it better.